1986
DOI: 10.1136/gut.27.5.499
|View full text |Cite
|
Sign up to set email alerts
|

Opposite effects of bombesin on insulin and gastrin response to food in humans.

Abstract: SUMMARY The effect of bombesin on insulin and gastrin response to a standard labelled meal was studied in eight healthy male volunteers. The gastric emptying of solids was simultaneously evaluated. During intravenous infusion of the peptide (5 ng/kg/min) the insulin release after eating was greatly reduced whereas food stimulated gastrin release was significantly enhanced. Both effects of bombesin are likely to be connected with the marked inhibition of gastric emptying induced by the peptide.Bombesin is a fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…This finding was not unexpected, taking into account our previous results con cerning meal-stimulated insulin release [41], The lack of postprandial hyperglycemia and the consequent inhibition of insulin release are likely to be connected with the strong inhibition of gastric emptying, the delay of which slows the entry of glucose into the small bowel. In accordance with our results, Salera et al [39] recently reported that dur ing bombesin administration to healthy vol unteers, the oral glucose load was followed by a flattened glucose curve and a significant inhibition of insulin release.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…This finding was not unexpected, taking into account our previous results con cerning meal-stimulated insulin release [41], The lack of postprandial hyperglycemia and the consequent inhibition of insulin release are likely to be connected with the strong inhibition of gastric emptying, the delay of which slows the entry of glucose into the small bowel. In accordance with our results, Salera et al [39] recently reported that dur ing bombesin administration to healthy vol unteers, the oral glucose load was followed by a flattened glucose curve and a significant inhibition of insulin release.…”
Section: Discussionmentioning
confidence: 83%
“…In this investigation, the delaying effect ex erted on the gastric emptying of liquids (glu cose solution) by bombesin was confirmed using a different (radioisotopic) technique. Looking at the emptying half-times for solids (previously obtained [41]) and liquids (re ported here), one can realize that the effects exerted by the peptide on the gastric emptying of liquids and solids are equally important, and this suggests that both the proximal and the distal stomach are involved in the action of bombesin on gastric emptying [31]. Although no effect on basal insulin levels was observed after bombesin administra tion, a clear-cut enhancement of insulin re lease was evident when glucose was injected intravenously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous papers, we have shown that bombesin affects the insulin response to mixed meal (Scarpignato & Micali, 1986) and to oral as well as intravenous glucose load (Scarpignato et al, 1987b). However, no effect on basal insulin levels was observed.…”
Section: Introductionmentioning
confidence: 94%
“…(2) Bombe sin delays gastric emptying [11][12][13]. Many of the effects of bombesin on motility appear to be indirectly mediated and bombesin may be an excitatory transmitter of an enteric inter neuron.…”
Section: Introductionmentioning
confidence: 99%